The “Arab Spring Index”. Analyzing the democratization of the Tunisian Revolution through the Political Opportunity Theory (2020)
Under the Political Process Theory, political opportunities comprise a very strong conceptual tool for understanding the emergence of collective action initiatives, i.e. riots, protests, strikes, etc. Political opportunities focus on the world “outside” social movements as, according to this theory, certain political demonstrations can emerge depending on the political context; hence, studying the different dimensions of political opportunities could improve our understanding of why certain movements are successful and others do not thrive. The Arab Spring revolutions have been studied from a myriad of perspectives, and although some authors tacitly analyze the contextual factors that have ignited protests, little attention has been given to political opportunities as a separate category for analysis. Consequentially, this article develops an exploration of the outcomes of the Arab Spring posing “political opportunities” at the core of the enquiry. More concretely, the article studies the case of Tunisia and explores a key dimension of political opportunities: openness to citizens’ participation. Tunisia represents a successful attempt of political change from authoritarianism to democracy and it is relevant to study how different dimensions of political opportunity changed since the irruption of the Arab Spring. The article is divided as follows: the first section develops a contextualization of the Arab Spring uprising, highlighting, on the one hand, the most relevant events and, on the other hand, how several academics have analyzed its development and consequences. Then, the chapter analyzes the Tunisia case, in order to better understand the specificities of the Arab Spring uprisings in this country. The following section develops the theoretical framework based on the political opportunities structure and, after establishing its relevance for better understanding the Arab Spring, there is an operationalization of the dimension “openness to citizens’ participation” using the Varieties of Democracy research project. Then, the next section analyzes each individual indicator for the case of Tunisia. Finally, the concluding remarks are developed, stating that openness to citizens’ participation was a key element to better understand the relative success of the Arab Spring in Tunisia